2016
DOI: 10.1123/jis.2015-0055
|View full text |Cite
|
Sign up to set email alerts
|

Coaches’ Perceptions of the Reduction of Athletic Commitment for Division II Student-Athletes: Development and Validation of a Measure of Athletic/Academic Balance

Abstract: Growing concerns exist regarding the amount of time student-athletes spend honing their athletic craft at the potential expense of their academic pursuits. Recently, the National Collegiate Athletic Association (NCAA) Division II Management Council approved the Life in the Balance (LITB) initiative to allow student-athletes more time for academics and other extracurricular activities beyond their sport(s). The purpose of this study was to develop a reliable and valid measurement scale assessing coaches' percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…Academic performance is a significant source of stress for most college students (Aquilina, 2013 ; López de Subijana et al, 2015 ; de Brandt et al, 2018 ; Davis et al, 2019 ). This stress may be further compounded among collegiate athletes based on their need to be successful in the classroom, while simultaneously excelling in their respective sport (Aquilina, 2013 ; López de Subijana et al, 2015 ; Huml et al, 2016 ; Hamlin et al, 2019 ). Davis et al ( 2019 ) conducted surveys on 173 elite junior alpine skiers and reported significant moderate to strong correlations between perceived stress and several variables including depressed mood ( r = 0.591), sleep disturbance ( r = 0.459), fatigue ( r = 0.457), performance demands ( r = 0.523), and goals and development ( r = 0.544).…”
Section: Academic Stressmentioning
confidence: 99%
“…Academic performance is a significant source of stress for most college students (Aquilina, 2013 ; López de Subijana et al, 2015 ; de Brandt et al, 2018 ; Davis et al, 2019 ). This stress may be further compounded among collegiate athletes based on their need to be successful in the classroom, while simultaneously excelling in their respective sport (Aquilina, 2013 ; López de Subijana et al, 2015 ; Huml et al, 2016 ; Hamlin et al, 2019 ). Davis et al ( 2019 ) conducted surveys on 173 elite junior alpine skiers and reported significant moderate to strong correlations between perceived stress and several variables including depressed mood ( r = 0.591), sleep disturbance ( r = 0.459), fatigue ( r = 0.457), performance demands ( r = 0.523), and goals and development ( r = 0.544).…”
Section: Academic Stressmentioning
confidence: 99%
“…While the pressure to win is similar to Division I coaches at Division II schools have a greater role in the academic success of their students because the department is unable to staff individuals who specialize in academic support (Nite, 2012). This lack of funding requires coaches and others within the athletics department to work together to provide adequate academic support (Huml et al, 2015).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…The academic success of student-athletes has been the focus of several previous studies (Berry, 2014;Foster & Huml, 2017;Huml et al, 2015;Navarro, 2015;Nite, 2012). The first area that is influential in academic success is the availability of resources to support the educational mission.…”
Section: Determinants Of Academic Successmentioning
confidence: 99%
See 2 more Smart Citations